Lung - Kelsey, Christopher R. (ALERT • Adverse Late Effects of Cancer Treatment, 2013)
The lungs are particularly sensitive to RT, and are often the primary dose-limiting structure during thoracic therapy. The alveolar/capillary units and pneumocytes within the alveoli appear to be particularly sensitive to RT. Hypoxia may be important in the underlying physiology of RT-associated lung injury. The cytokine transforming growth factor-beta (TGF-β), plays an important role in the development of RT-induced fibrosis. The histopathological changes observed in the lung after RT are broadly characterized as diffuse alveolar damage. The interaction between pre-treatment PFTs and the risk of symptomatic lung injury is complex. Similarly, the link between changes in PFTs and the development of symptoms is uncertain. The incidence of symptomatic lung injury increases with increase in most dosimetric parameters. The mean lung dose (MLD) and V20 have been the most-often considered parameters. MLD might be a preferable metric since it considers the entire 3D dose distribution. Radiation to the lower lobes appears to be more often associated with clinical symptoms than is radiation to the upper lobes. This might be related to incidental cardiac irradiation. In pre-clinical models, there appears to be a complex interaction between lung and heart irradiation. TGF-β has been suggested in several studies to predict for RT-induced lung injury, but the data are still somewhat inconsistent. Oral prednisone (Salinas and Winterbauer 1995), typically 40–60 mg daily for 1–2 weeks with a slow taper, is usually effective in treating pneumonitis. There are no widely accepted treatments for fibrosis. A number of chemotherapeutic agents have been suggested to be associated with a range of pulmonary toxicities.